The Hard Power Limitation: The Failure of Russia to Bring Back the Great Power Status - Sungkar, Najmi; Avianto, Wishnu; Syawfi, Idil (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2024)
This journal provides a comprehensive examination of the evolving dynamics surrounding Russia's rise in global power and the challenges it encounters in aligning with Vladimir Putin's vision. By using the Smart Power concept, which uses military power and diplomacy to achieve goals on the international stage, it is known as